Study of Knowledge, Attitude, and Practice of Self-medication in Riobamba, Ecuador based on an Indeterminate Likert Scale - Lizbeth Geovanna Silva-Guayasamín; Zully Mayra Romero-Orellana; Lisbeth Josefina Reales-Chacón; Isaac Germán Pérez-Vargas; Sulema de la Caridad Hernández-Batista; Carlos Antonio Escobar-Suárez; María José López-Pino; Josselyn Gabriela Bonilla-Ayala (Neutrosophic Sets and Systems)
Self-medication (SM) is a significant public health problem in Riobamba, Ecuador, characterized by the use of drugs without a prescription. This practice carries risks such as inappropriate drug use and antimicrobial resistance. This study assesses the prevalence, associated factors, and attitudes towards SM in Riobamba. To do so, data were collected from 383 city residents, who also responded to a survey. To ensure the accuracy of the results, we asked respondents to answer some questions based on an Indeterminate Likert Scale. In this way, people can evaluate each of the different opinions, thus obtaining a more reliable result of the person's opinion, compared to the classic Likert scale. In addition, the Neutrosophic Similarity theory is used to convert the responses to a nominal scale.